Social harmonization and labor market performance in Europe - Katarzyna Mirecka; Izabela Styczyńska (Center for Social and Economic Research (CASE), 2017)
The paper aims to assess the impact of selected elements of social harmonization on labor market performance in the European Union among two groups of workers - the total working population and the elderly. The aim is to examine whether upward changes in labor taxes affect employment, unemployment, and inactivity rates in the European Union. The descriptive empirical evidence shows that the level of labor taxation varies significantly across European countries and the introduced changes might affect national markets differently. The Arellano-Bond dynamic panel data regression shows that an increase in the tax wedge, as an element of a social harmonization process, has a very weak impact on labor market performance in the European Union. The impact is statistically significant and negative only for the elderly (i.e. the population aged 50+). Empirical analysis suggests that upward social convergence might negatively affect the employment of the most disfavored groups in the labor market, such as the elderly. It suggests that social harmonization focused on reducing the tax wedge would have favorable effects on labor market performance, especially among the most disadvantaged groups.
Keywords: J31; J32; C23; J38; J41; J61; H53; H55; 330; employment of the elderly; minimum wage; social security contributions; labor tax; Social Europe